Associations between usual diet and gut microbiota composition: results from the Milieu Intérieur cross-sectional study. Issue 5 (24th April 2019) - Partula, Valentin; Mondot, Stanislas; Torres, Marion J; Kesse-Guyot, Emmanuelle; Deschasaux, Mélanie; Assmann, Karen; Latino-Martel, Paule; Buscail, Camille; Julia, Chantal; Galan, Pilar; Hercberg, Serge; Rouilly, Vincent; et al.
ABSTRACT: Background: Diet is widely recognized as one of the main modifiable drivers of gut microbiota variability, and its influence on microbiota composition is an active area of investigation. Objective: The present work aimed to explore the associations between usual diet and gut microbiota composition in a large sample of healthy French adults. Methods: Gut microbiota composition was established through sequencing of the 16S rRNA gene in stool samples from 862 healthy French adults of the Milieu Intérieur study. Usual dietary consumptions were determined through the administration of a food-frequency questionnaire. The associations between dietary variables and α- and β-diversity indexes and relative taxa abundances were tested using Spearman correlations, permutational ANOVAs, and multivariate analyses with linear models, respectively. Results: Foods generally considered as healthy (raw fruits, fish) were positively associated with α-diversity, whereas food items for which a limited consumption is generally recommended (fried products, sodas or sugary drinks, fatty sweet products, processed meats, ready-cooked meals, and desserts) were negatively associated with α-diversity. Fruits, fried products, ready-cooked meals, and cheese contributed to shifts within microbiota composition (β-diversity). Our results also highlighted a number of associations between various food group intakes and abundances of specific phyla, genera, and species. For instance, the consumption of cheese was negatively associated with Akkermansia muciniphila abundance. Conclusions: This large-scale population-based study supports that the usual consumption of certain food items is associated with several gut microbial features, and extends the mechanistic arguments linking Western diet to an altered microbiota composition. These results provide new insights into the understanding of complex diet–gut microbiota relations, and their implications for host health deserve further investigation because altered microbiota diversity was consistently linked to increased risk of several health outcomes. This trial was registered at clinicaltrials.gov as NCT01699893.